Ta có :\(\frac{6}{x^2+2}+\frac{12}{x^2+8}=3-\frac{7}{x^2+3}\)
\(\Leftrightarrow\frac{6}{x^2+2}+\frac{12}{x^2+8}+\frac{7}{x^2+3}=3\)
\(\Leftrightarrow\left(\frac{6}{x^2+2}-1\right)+\left(\frac{12}{x^2+8}-1\right)+\left(\frac{7}{x^2+3}-1\right)=0\)
\(\Leftrightarrow\frac{4-x^2}{x^2+2}+\frac{4-x^2}{x^2+8}+\frac{4-x^2}{x^2+3}=0\)
\(\Leftrightarrow\left(4-x^2\right)\left(\frac{1}{x^2+2}+\frac{1}{x^2+8}+\frac{1}{x^2+3}\right)=0\)
Ta thấy : \(\frac{1}{x^2+2}+\frac{1}{x^2+8}+\frac{1}{x^2+3}\ne0\forall x\)
Do đó : \(4-x^2=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\\x=-2\end{cases}}\) ( thỏa mãn )
Vậy : \(x\in\left\{-2,2\right\}\)